Pedagogical translation as a strategy for learning metaphorical utterances in the context of Spanish as a specialized language - Ureña Tormo, Clara; Valero Fernández, Pilar (Círculo de Lingüística Aplicada a la Comunicación, 2025)
With the advent of the Communicative Method, translation suffered an absolute veto due to its traditional link with the Grammar-Translation Method. However, its reincorporation in language classrooms, particularly in the field of Spanish as a foreign language (SFL), has been verified. This study analyzes students’ evaluation and use of pedagogical translation (PT) as a learning strategy for metaphorical utterances (ME), which are common multiword units in specialized languages. For this purpose, a group of 54 university students at B2 level were distributed in two learning contexts: one with linguistic immersion (Universitat Politècnica de València) and the other without immersion (Universität Tübingen). The most striking results show that 70.3 % of the participants always or almost always translate words to their L1 when they learn new vocabulary, and 44.4 % think that PT always or almost always helps them to learn EM. A high percentage use PT to explain the meaning of EM instead of a definitional paraphrase in Spanish, both when the EM is known (75.84 %) and when it is not known (73.99 %). In addition, 64.7 % select translation in a bilingual dictionary or translator as the main learning strategy to retrieve the meaning of an EM. It has also been verified that the degree of semantic transparency of the EM does not influence the type of strategy used to access their meaning (p = .694). Keywords: pedagogical translation; metaphorical utterances; specialized languages; learning strategy.